Patient experience of the Electronic Health Record (EHR) in a maternity unit in Ireland - Joye McKernan; Paul Corcoran; Richard Greene (Patient Experience Journal, 2022)
The introduction of the Electronic Health Records (EHRs) for maternity services in Ireland provided an opportunity to examine patient satisfaction and to examine what patients require from an Electronic Health Record. The implementation of the EHR in Ireland started in 2016, and at present, four of the 19 maternity units are digital. Patients at antenatal booking visits in an Irish maternity unit were invited to participate in the project. The invite was taken up by 201 women. The survey took 10-15 minutes to complete. The survey was conducted nine months following the implementation of the MN-CMS. The survey was anonymous and was divided into three distinctive sections; participant information, regarding the staff encounters on their visits and questions about the new system. 70% of participants rated their overall consultation from very good to outstanding. 73% of participants believe the computer system will ensure quality of care. Participants believe their personal information is safe (65%) in the new computer system. Over 75% of participants did not have any concerns regarding the new computer system. Eighty-one percent of participants noted that they would like access online to their charts and 91% of these respondents would like access to the full chart. Patients in this study were very receptive to the introduction of EHR and noted that it would be beneficial for their care. They also noted the impact the EHR could have on clinic time and interactions with staff. However, patients require access to their charts this they believe would provide them with ownership of their health. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Innovation%20%26%20Technology%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens